Translation, reliability and validity of the job satisfaction scale in a sample of portuguese fitness professionals - Ramos, Liliana (2020)
This study aimed to translate and validate the job satisfaction scale (JSS) to Portuguese fitness professionals. A total of 418 fitness professionals (210 male; 208 female) with an average age of 30.9 ± 6.5 years and a professional experience of 7.72 ± 9.1 years participated in this study. Before conducting a confirmatory factor analysis (CFA), we designed a test-retest analysis to determine reliability. Cronbach’s alpha demonstrated satisfactory internal consistency (.96), which revealed a high degree of temporal reliability. The confirmatory analyses supported a unidimensional model (1 factor/16 item) of the JSS in terms of model adequacy coefficients. In conclusion, we found that the measurement model (1 factor/16 items) of the translation and validation of the JSS for Portuguese fitness professionals had highly acceptable psychometric properties and can be used in future to access their job satisfaction.